Covid-19 Pandemic as an Event of Force Majeure in Agreements (Case Study of Indonesian Court Decisions) - Fadlan, Mochamad Lailul; Fidhayanti, Dwi (University of Darusssalam Gontor, 2024)
The legal uncertainty regarding the categorization of the regarding whether or not the Covid-19 pandemic Covid-19 pandemic as a force majeure condition has led to inconsistent interpretations for those directly impacted by the situation. Therefore, considerations can be accepted as a reason for force majeure in agreements need further analysis, both in terms of written law and judicial practice. The objective of this research is to determine the legitimacy of the Covid-19 pandemic as force majeure condition and to describe the basis of the court’s reasoning in deciding whether the pandemic can be accepted as a valid reason for force majeure in contractual agreements. This research adopts a normative juridical methodology, utilizing a statue approach, case approach, and conceptual approach. The findings reveal that the Covid-19 pandemic may be considered as force majeure, provided that the debtor (in the contract) can demonstrate fulfillment of the force majeure criteria as stipulated in Article 1244-1245 of the Indonesian Civil Code, as well as the International Chamber of Commerce’s Force Majeure and Hardship Clauses. In practice, in determining whether the Covid-19 pandemic qualifies as force majeure, the court evaluates whether the following elements are satisfied, the event is unexpected (i.e., the Covid-19 pandemic), the event is beyond the debtor’s control, there is no element of negligence of intent, and there is good faith in the part of the debtor.